2023
DOI: 10.1038/s41419-023-05646-x
|View full text |Cite
|
Sign up to set email alerts
|

NSUN2 promotes osteosarcoma progression by enhancing the stability of FABP5 mRNA via m5C methylation

Abstract: Abstract5-methylcytosine (m5C) modification, which is mainly induced by the RNA methyltransferase NSUN2 (NOP2/Sun domain family, member 2), is an important chemical posttranscriptional modification in mRNA and has been proven to play important roles in the progression of many cancers. However, the functions and underlying molecular mechanisms of NSUN2-mediated m5C in osteosarcoma (OS) remain unclear. In this study, we found NSUN2 was highly expressed in OS tissues and cells. We also discovered that higher expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…NSun2 is hitherto the best studied m5C writer, and many reports have suggested that NSun2‐mediated RNA methylation plays a strong oncogenic role in multiple pan‐caner pathways, including cancer cell proliferation, migration, invasion, and drug resistance 61,62 . Most recently, NSun2 was demonstrated to methylate FABP5 mRNA thus promoting fatty acid metabolism and osteosarcoma progression, 63 which unambiguously broadens our understanding of osteosarcoma biology. In line with this, NSun2 deficiency in our work was also observed to hinder osteosarcoma cell growth before the treatment of doxorubicin (Figures 9J and S2).…”
Section: Discussionmentioning
confidence: 97%
“…NSun2 is hitherto the best studied m5C writer, and many reports have suggested that NSun2‐mediated RNA methylation plays a strong oncogenic role in multiple pan‐caner pathways, including cancer cell proliferation, migration, invasion, and drug resistance 61,62 . Most recently, NSun2 was demonstrated to methylate FABP5 mRNA thus promoting fatty acid metabolism and osteosarcoma progression, 63 which unambiguously broadens our understanding of osteosarcoma biology. In line with this, NSun2 deficiency in our work was also observed to hinder osteosarcoma cell growth before the treatment of doxorubicin (Figures 9J and S2).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, a novel NSUN2 lncRNA (NMR) methylated by m 5 C, which was detected to be upregulated in esophageal squamous cell carcinoma (ESCC) and functioned as a key regulator of ESCC tumor metastasis and drug resistance, was identified to be possible diagnostic biomarker of ESCC . A study reported recently has found that the level of expression of FABP5 could be increased by NSUN2 through stabilizing FABP5 mRNA via m 5 C; accordingly, fatty acid metabolism in osteosarcoma (OS) cells and the progression of OS were also promoted, suggesting NSUN2 as a practical biomarker for OS patients . In addition, Blanco et al indicated that tRNA hypomethylation due to knockdown or knockout of NSUN2 enabled tRNA cleavage mediated by angiogenin and caused the enrichment of 5′-tRNA fragments, which activated stress response pathways that initiate decreased protein translation rates as well as cell size with incremental cell death, thus inducing a syndromic disorder with growth and neurodevelopmental deficiencies in humans .…”
Section: Diagnostic Relationship Between Nucleic Acid Modification An...mentioning
confidence: 99%
“…89 A study reported recently has found that the level of expression of FABP5 could be increased by NSUN2 through stabilizing FABP5 mRNA via m 5 C; accordingly, fatty acid metabolism in osteosarcoma (OS) cells and the progression of OS were also promoted, suggesting NSUN2 as a practical biomarker for OS patients. 90 In addition, Blanco et al indicated that tRNA hypomethylation due to knockdown or knockout of NSUN2 enabled tRNA cleavage mediated by angiogenin and caused the enrichment of 5′-tRNA fragments, which activated stress response pathways that initiate decreased protein translation rates as well as cell size with incremental cell death, thus inducing a syndromic disorder with growth and neurodevelopmental deficiencies in humans. 91 Apart from NSUN2, the roles of NSUN6 in suppressing cell proliferation and PC tumor growth were verified because the level of NSUN6 in healthy pancreatic tissues was decreased compared to that in PC tissues, thus implying NSUN6 performed well in evaluating tumor recurrence and survival among PC patients.…”
Section: ■ Introductionmentioning
confidence: 99%
“…NSUN2‐mediated m 5 C modification promotes hypo‐differentiation of HCC 23 . Besides, NSUN2‐mediated m 5 C methylation promotes osteosarcoma progression by enhancing the stability of FABP5 mRNA 24 . Bioinformatic analysis revealed that NSUN2 promote LUAD progression and was associated with the infiltration levels of immune cells.…”
Section: Introductionmentioning
confidence: 97%
“…23 Besides, NSUN2-mediated m 5 C methylation promotes osteosarcoma progression by enhancing the stability of FABP5 mRNA. 24 Bioinformatic analysis revealed that NSUN2 promote LUAD progression and was associated with the infiltration levels of immune cells. Overexpression of NSUN2 promotes the proliferation and migration of A549 cells.…”
Section: Introductionmentioning
confidence: 99%